2012
DOI: 10.1002/pro.2015
|View full text |Cite
|
Sign up to set email alerts
|

Structures of dimethylsulfoniopropionate‐dependent demethylase from the marine organism Pelagabacter ubique

Abstract: Dimethylsulfoniopropionate (DMSP) is a ubiquitous algal metabolite and common carbon and sulfur source for marine bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…Roseobacters are a group of abundant marine bacteria known to demethylate DMSP, and Pelagibacter belongs to the SAR11 clade, whose members are highly dominant organisms in marine ecosystems, that are also well known to demethylate DMSP [11] and for which the dmdA protein structure is described. [59] The low sequence variation detected in our clone libraries, and the fact that a large fraction of bacterial dmdA taxonomic diversity was shared between all three coral host species sampled, suggest the absence of endemic dmdA assemblages or strict species-specific coral niches for DMSP demethylating bacteria within the surface mucus layer of corals. A recent study comparing free-living v. particle-associated bacterial dmdA assemblages found that most dmdA genes were shared between these two habitats, [42] again suggesting no niche diversification of dmdA gene assemblages towards distinct habitats.…”
Section: Phylogenetic Affiliation Of Bacterial Dmda Gene Assemblages mentioning
confidence: 73%
“…Roseobacters are a group of abundant marine bacteria known to demethylate DMSP, and Pelagibacter belongs to the SAR11 clade, whose members are highly dominant organisms in marine ecosystems, that are also well known to demethylate DMSP [11] and for which the dmdA protein structure is described. [59] The low sequence variation detected in our clone libraries, and the fact that a large fraction of bacterial dmdA taxonomic diversity was shared between all three coral host species sampled, suggest the absence of endemic dmdA assemblages or strict species-specific coral niches for DMSP demethylating bacteria within the surface mucus layer of corals. A recent study comparing free-living v. particle-associated bacterial dmdA assemblages found that most dmdA genes were shared between these two habitats, [42] again suggesting no niche diversification of dmdA gene assemblages towards distinct habitats.…”
Section: Phylogenetic Affiliation Of Bacterial Dmda Gene Assemblages mentioning
confidence: 73%
“…(B) Although overall architecture and H 4 folate conformation is conserved, LigM and its homologs differ to some degree in the precise folateprotein interactions that they use. Homologs shown for comparison include dimethylsulfoniopropionate(DMSP)-dependent demethylase (DmdA), which catalyzes the transfer of a methyl from DMSP to H 4 folate-N 5 (PDB ID code: 3TFJ) (27); Tm_T, a glycine cleavage system T-protein that catalyzes the formation of 5,10-methylene-H 4 folate and ammonia from an H-proteinassociated aminomethyl moiety (PDB ID code: 1WOO) (11); and dimethylglycine oxidase (DMGO), which oxidizes N,N-dimethyl glycine to form 5,10-methylene-H 4 folate (PDB ID code: 1PJ7) (20). Key interaction residues are shown in bold black type for LigM, in red type for DmdA, in blue type for Tm_T, and in green type for DMGO.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond LigM's unconventional use of glutamine residues in binding H 4 folate, there are several additional striking differences between the residue topology of LigM's H 4 folate-binding site and those of its closest structural homologs Tm_T (rmsd: 2.4 Å, 23% sequence identity) (11); Arthrobacter globiformis dimethylglycine oxidase (DMGO) (rmsd: 2.7 Å, 21% sequence identity) (20); and dimethylsulfoniopropionate (DMSP)-dependent demethylase (DmdA) (rmsd: 3.2 Å, 20% sequence identity) (27). Notably, LigM contains phenylalanines (Phe110, Phe188) and a tryptophan (Trp256) in place of three key Tm_T tyrosines (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations